Enhancing the Antiviral Efficacy of RNA-Dependent RNA Polymerase Inhibition by Combination with Modulators of Pyrimidine Metabolism. Issue 6 (18th June 2020) - Liu, Qi; Gupta, Amita; Okesli-Armlovich, Ayse; Qiao, Wenjie; Fischer, Curt R.; Smith, Mark; Carette, Jan E.; Bassik, Michael C.; Khosla, Chaitan
Summary: Genome-wide analysis of the mode of action of GSK983, a potent antiviral agent, led to the identification of dihydroorotate dehydrogenase as its target along with the discovery that genetic knockdown of pyrimidine salvage sensitized cells to GSK983. Because GSK983 is an ineffective antiviral in the presence of physiological uridine concentrations, we explored combining GSK983 with pyrimidine salvage inhibitors. We synthesized and evaluated analogs of cyclopentenyl uracil (CPU), an inhibitor of uridine salvage. We found that CPU was converted into its triphosphate in cells. When combined with GSK983, CPU resulted in large drops in cellular UTP and CTP pools. Consequently, CPU-GSK983 suppressed dengue virus replication in the presence of physiological concentrations of uridine. In addition, the CPU-GSK983 combination markedly enhanced the effect of RNA-dependent RNA polymerase (RdRp) inhibition on viral infection. Our findings highlight a new host-targeting strategy for potentiating the antiviral activity of RdRp inhibitors. Graphical Abstract: Highlights: Cyclopentenyl uracil and analogs inhibit pyrimidine salvage in vitro and in cells A host-targeting antiviral strategy combining DHODH inhibitors with CPU is explored The strategy rescues the antiviral efficacy of a DHODH inhibitor in 20 μM uridine Modulating pyrimidine metabolism boosts the antiviral activity of an RdRp inhibitor Abstract : Many RNA virus infections lack suitable treatments. Liu et al. identified a host-targeting antiviral strategy of modulating pyrimidine metabolism with cyclopentenyl uracil, an inhibitor of pyrimidine salvage, and GSK983, an inhibitor of de novo biosynthesis. This combination also increased the potency of an RNA-dependent RNA polymerase inhibitor, against dengue virus.